Firm Value from Intellectual Capital Disclosure and Financial Ratios Perspective - Ni Gusti Ayu Gede Ratih Aprilia; Luh Komang Merawati; Daniel Raditya Tandio (Jurnal Riset Akuntansi Terpadu, 2023)
This study aims to test and obtain empirical evidence of the effect of intellectual capital disclosure, profitability, dividend policy, investment decisions, and company size on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The type of research using the a quantitative research. The research method uses secondary data. The population in this study were 196 manufacturing companies listed on the IDX for 2019-2021 with a sample of 175 manufacturing companies with 3 research periods, making 525 observations using purposive sampling. The analytical method uses multiple linear regression analysis. The results of the study show that intellectual capital disclosure, profitability, and investment decisions have a positive effect on firm value, meanwhile dividend policy and company size have no effect on firm value.